Unconferencing methodology as a cultural disrupter in higher education: Enabling reflections on promoting inclusivity, diversity, and equitable spaces - Govender, Rosaline; Jacobs, Anthea; Malebo, Ntsoaki (Critical Studies in Teaching and Learning, 2024)
In applying the collective mind to challenges in higher education, there is hope for innovative solutions. HELTASA’s approach to adapting the unconference methodology during the annual learning and teaching (un)conference in 2021 demonstrated its vision to reflect on a re-imagined inclusive higher education using the questions: Sivela phi? (where do we come from?), Si phi? (where we are?), and Siya phi? (where are we going?). This paper reflects on how the unconferencing methodology was used as a cultural disrupter during the HELTASA’s (un)conference. We identify with ‘culture’ as emphasising active meaning-making instead of unchanging, static ideas by homogenous groups. ‘Culture’ is dynamic, and it changes over time. In the context of unconferencing methodology, cultural disruption refers to a deliberate effort to challenge and disrupt traditional cultural norms and values to promote greater inclusivity, diversity, creativity and problem-solving. The unconference is intended to disrupt current thinking and practices in conferences and open higher education spaces for creative, critical dialogue and innovation. Cultural disruption plays a transformative role in deconstructing established norms of knowledge, identity, and practices within higher education. The unconference seeks to challenge the prevailing power dynamics inherent in higher education and mirrored in traditional conferences by adopting a participant-driven and focused approach. The unconference supports the notion of collective thinking or collaboration, which re-frames knowledge boundaries as dynamic inter-relationships with due weight given to reflective ways of knowing (Brown, 2015). This paper uses the Reflection and Critical Thinking Model by Mugumbate, et al. (2021) as a framework to explore and understand how cultural disruptions were implemented and experienced during the planning and execution of the (un)conference itself. This paper critically reflects on the HELTASA (un)conference Call, cultural representations, presentation types, and structure of the unconference to share possible cultural disruptions. This paper's reflections delve into the effectiveness of unconferencing in higher education as a potent tool for cultural disruption in relation to power dynamics, participation, individual and collective thinking, and the imperative of amplifying diverse voices. Unconferencing, through its disruption of cultural norms and values, can promote greater innovation and creativity by enabling the incorporation of a wider range of perspectives and ideas. Additionally, unconferencing can create more inclusive and equitable spaces where traditionally marginalised voices are provided a platform to be heard and represented.